Satisfactory Outcomes and Improved Range of Motion With Arthroscopic Lysis of Adhesions and Manipulation for Arthrofibrosis After Multiligamentous Knee Reconstruction - Abhinav Lamba, B.S; Alexander M. Boos, B.A; Aaron J. Krych, M.D; Michael J. Stuart, M.D; Mario Hevesi, M.D., Ph.D; Bruce A. Levy, M.D (Elsevier, 2023)
Purpose: To (1) evaluate the efficacy of surgery for arthrofibrosis (AF), as measured by preoperative and postoperative range of motion (ROM), and (2) evaluate patient-reported outcomes at mid- to long-term follow-up. Methods: We performed a retrospective review of a prospectively collected database including patients who sustained multiligamentous knee injuries (MLKIs) managed surgically, sustained loss of ROM after surgical intervention, and underwent subsequent lysis of adhesions (LOA) and/or manipulation under anesthesia (MUA). Loss of ROM was defined as clinically symptomatic loss of terminal extension (flexion deformity) and/or flexion compared with the contralateral side. Results: In total, 12 patients (6 male and 6 female patients; age, 36.0 ± 8.7 years; body mass index, 36.3 ± 8.7) met the inclusion criteria and underwent LOA and/or MUA at a mean of 14 ± 27 months (median, 4.0 months; interquartile range, 3.5-9.3 months) after MLKI surgery. Prior to AF intervention, patients showed mean flexion of 75.9° ± 36.0° (range, 30°-129°), mean extension of 3.2° ± 5.2° (range, 0°-12°), and a mean arc of motion of 72.7° ± 34.1° (range, 30°-117°). At a mean follow-up of 7.0 ± 3.9 years (range, 2.4-16.6 years) after AF intervention, patients showed a significant increase in knee flexion of 49° (P = .003), a significant increase in arc of motion of 51° (P = .002), and an increase in extension of 3° (P = .086). The mean final International Knee Documentation Committee score was 59.5 ± 23.9; Lysholm score, 72.1 ± 20.6; Tegner activity scale score, 5.6 ± 2.8; visual analog scale score at rest, 1.0 ± 1.6; and visual analog scale score with use, 3.3 ± 2.5. At final follow-up, 2 patients (17%) had undergone conversion to total knee arthroplasty (TKA) at 10.3 and 24.8 years after MLKI surgery. Of the 10 patients who did not go on to TKA, 9 (90%) reported that they were satisfied or very satisfied with their AF knee surgery. Conclusions: At mid-term follow-up, LOA and/or MUA for symptomatic AF after multiligamentous knee surgery results in high rates of patient satisfaction and improved knee ROM and pain scores, as well as durable and satisfactory functional outcomes in patients not undergoing TKA. Level of Evidence: Level IV, therapeutic case series.